A Spinozist Defense on Freedom of Conscience - Liu, Jinze (Transactions on Social Science, Education and Humanities Research, 2024)
Spinoza tried to defend freedom of conscience in his political writings. To this end, he offers two arguments, one negative and the other positive. Negative arguments emphasize that a person’s right to judgment cannot be completely eradicated, and positive arguments emphasize the utility of protecting freedom of conscience. I argue that if Spinoza wants to criticize tyranny, he must emphasize positive arguments, even though he emphasizes negative ones more. I respond to Curley’s criticism of Spinoza by emphasizing positive argument.